2004
DOI: 10.1002/bdm.468
|View full text |Cite
|
Sign up to set email alerts
|

Improving judgement with prepaid expert advice

Abstract: Decision makers (''Judges'') often make decisions after obtaining advice from an Advisor. The two parties often share a psychological ''contract'' about what each contributes in expertise to the decision and receives in monetary outcomes from it. In a laboratory experiment, we varied Advisor Experitise and the opportunity for monetary rewards. As expected, these manipulations influenced advice quality, advice taking, and Judge post-advice decision quality. The main contribution of the study, however, was the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 42 publications
(54 reference statements)
4
107
0
4
Order By: Relevance
“…Individuals commonly weigh advice received from experienced and knowledgeable advisors more heavily than advice received from advisors with less experience or expertise (Goldsmith & Fitch, 1997;Feng & MacGeorge, 2006;Harvey & Fischer, 1997;Sniezek, Schrah, & Dalal, 2004;Yaniv, 2004;Yaniv & Kleinberger, 2000;Yaniv & Milyavsky, 2007). Although this research has focused on advice taking in dyadic interactions, related studies have examined the influence of knowledgeable and expert team members and have found similar effects on decision quality in team settings (see Hollenbeck, Ilgen, LePine, Colquitt, & Hedlund, J., 1998;Hollenbeck, Ilgen, Sego, Hedlund, Major, & Phillips, 1995;Humphrey, Hollenbeck, Meyer, & Ilgen, 2002).…”
Section: The Role Of Advisor Experience and Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals commonly weigh advice received from experienced and knowledgeable advisors more heavily than advice received from advisors with less experience or expertise (Goldsmith & Fitch, 1997;Feng & MacGeorge, 2006;Harvey & Fischer, 1997;Sniezek, Schrah, & Dalal, 2004;Yaniv, 2004;Yaniv & Kleinberger, 2000;Yaniv & Milyavsky, 2007). Although this research has focused on advice taking in dyadic interactions, related studies have examined the influence of knowledgeable and expert team members and have found similar effects on decision quality in team settings (see Hollenbeck, Ilgen, LePine, Colquitt, & Hedlund, J., 1998;Hollenbeck, Ilgen, Sego, Hedlund, Major, & Phillips, 1995;Humphrey, Hollenbeck, Meyer, & Ilgen, 2002).…”
Section: The Role Of Advisor Experience and Expertisementioning
confidence: 99%
“…Second, characteristics of the advisor can have an important influence on the extent of advice use. For example, research indicates that advice is weighted more heavily when advisors are relatively more experienced or knowledgeable than the decision makers (Goldsmith & Fitch, 1997;Feng & MacGeorge, 2006;Harvey & Fischer, 1997;Sniezek, Schrah, & Dalal, 2004;Yaniv, 2004;Yaniv & Kleinberger, 2000;Yaniv & Milyavsky, 2007) and when the advisors express greater confidence in the quality of their advice (Lawrence & Warren, 2003;Phillips, 1999;Sniezek & Buckley, 1995;Sniezek & Van Swol, 2001;Van Swol & Sniezek, 2005;Yaniv & Foster, 1997). Finally, aspects of the decision maker's internal states can impact the extent of advice-taking.…”
mentioning
confidence: 99%
“…Sniezek, Schrah, & Dalal, 2004;Yaniv, 2004a). One reason for this is that that the mere act of combining multiple recommendations increases accuracy because it decreases the random error associated with each separate opinion (Yaniv, 2004a, b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals weight advice more heavily when advisors are more experienced or more knowledgeable than the decision makers themselves (Goldsmith & Fitch, 1997;Feng & MacGeorge, 2006;Harvey & Fischer, 1997;Sniezek, Schrah, & Dalal, 2004;Yaniv, 2004;Yaniv & Kleinberger, 2000;Yaniv & Milyavsky, 2007). People are similarly more likely to weight advice when advisors express confidence in the quality of their advice (Sniezek & Buckley, 1995;Sniezek & Van Swol, 2001;Tost, Gino, & Larrick, in press;Van Swol & Sniezek, 2005;Yaniv, 1997).…”
Section: Advicementioning
confidence: 99%